Risk and ambiguity in a public good game - Van Driessche, Sarah; Boun My, Kene; Brunette, Marielle (Frontiers in Behavioral Economics, 2024)
In this paper, we analyze the effects of risk and ambiguity on the decisions to mitigate or to adapt to a threat. We run an experiment where every group of four subjects is exposed to a risk that may result in a loss for each member. Subjects must decide on the allocation of their resources between mitigation strategies that allow them to decrease the probability of a disaster occurring for the group, and adaptation strategies that allow them to reduce the magnitude of that disaster for themselves only. In a first treatment (called Risk), subjects perfectly know the probability of occurrence of the event. We introduce ambiguity with regard to that probability in a second treatment (called Ambiguity), and in a third treatment (called Information Acquisition), subjects have the possibility to pay to obtain information allowing them to eliminate ambiguity.The results show that the introduction of ambiguity has no impact on average contributions compared to the Risk treatment. However, individual decisions to mitigate or to adapt are affected by subjects' attitude toward risk and ambiguity. The latter also explains the willingness to pay to obtain information.